FORMULATION AND EVALUATION OF SOLUBILITY ENHANCED IN SITU GELLING EYE DROPS OF LOTEPREDNOL ETABONATE - NIKITA PRADEEP KHANDELWAL,; PRASHANT BHIDE,; REESHWA NACHINOLKAR, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of the present study is to improve the aqueous solubility and develop in situ gelling eye drops of loteprednol etabonate. Beta-cyclodextrin (β-CD)-assisted solubility enhancement was attempted and phase solubility studies were carried out. Methods: The kneading technique was used to formulate drug/β-CD inclusion complexes with a ratio of 1:1. In situ gelling ophthalmic sol–gel systems were then developed. Ion-sensitive and pH-dependent trigger mechanisms were targeted. The former type was based on increasing gellan gum concentration, to formulate three systems F1, F2, and F3. The latter pH-dependent systems were formulated using a constant concentration of Carbopol 971P NF and varying concentrations of hydroxypropyl methylcellulose (HPMC) K4 M and HPMC K15M grades giving formulations F4, F5, and F6. All six formulations were subjected to physicochemical evaluation for clarity and appearance, texture analysis, pH, viscosity, isotonicity, in vitro gelation, drug content determination, and microbiological tests (sterility testing and effectiveness of preservative) which were also conducted. Results: All the six formulations passed the analytical tests, with F2 and F4 emerging as the optimized formulations. Eight hour in-vitro drug release carried out in a fabricated diffusion cell revealed the release to a concentration dependent controlled one. One month stability studies at 40°C and 75% RH of the optimized formulations proved their robustness. Conclusion: Extensive studies carried out revealed the optimized formulation for each category of sol-gel systems. Formulations F2 and F4 were found to be these optimized formulations.